Experimental and quantum studies of newly synthesized pyridazinium derivatives on mild steel in hydrochloric acid medium. (2019) - El-Hajjaji, F.; Merimi, I.; Messali, M.; Obaid, R.J.; Salim, R.; Taleb, M.; Hammouti, B.
Abstract: The effect of three newly synthesized pyridine derivatives R3, R4 and R5 on the corrosion behaviour of steel in 1 M hydrochloric acid (HCl) solution was studied by gravimetric and electrochemical impedance spectroscopy (EIS) measurements, All compounds have shown good inhibition efficiency (IE %) in acidic medium at 298°K mostly for R3. The most effective molecule R3 is investigated in the temperature range from 308 to 328°C by impedance spectroscopy (EIS) method. Results obtained show that this compound is an effective inhibitor, its efficiency increased with inhibitor concentration to attain a value of 91% for 10 -3 M at 298°K and decreased with increasing of the temperature due to the faster and contentious dissolution of the metal surface with temperature. Furthermore, the corrosion performance of R3 on mild steel at different immersion times was studied. Electrochemical impedance spectroscopy (EIS) measurements revealed that the increase of immersion time from 1H to 24 H for the steel in the hydrochloric acid solution decreases the charge transfer resistance Rt and then the inhibition efficiency.